Monitoring HSP70 exosomes in cancer patients' follow up: a clinical prospective pilot study. Issue 1 (20th May 2020) - Chanteloup, Gaëtan; Cordonnier, Marine; Isambert, Nicolas; Bertaut, Aurélie; Hervieu, Alice; Hennequin, Audrey; Luu, Maxime; Zanetta, Sylvie; Coudert, Bruno; Bengrine, Leila; Desmoulins, Isabelle; Favier, Laure; et al.
ABSTRACT: Exosomes are nanovesicles released by all cells that can be found in the blood. A key point for their use as potential biomarkers in cancer is to differentiate tumour‐derived exosomes from other circulating nanovesicles. Heat shock protein‐70 (HSP70) has been shown to be abundantly expressed by cancer cells and to be associated with bad prognosis. We previously showed that exosomes derived from cancer cells carried HSP70 in the membrane while those from non‐cancerous cells did not. In this work, we opened a prospective clinical pilot study including breast and lung cancer patients to determine whether it was possible to detect and quantify HSP70 exosomes in the blood of patients with solid cancers. We found that circulating exosomal HSP70 levels, but not soluble HSP70, reflected HSP70 content within the tumour biopsies. Circulating HSP70 exosomes increased in metastatic patients compared to non‐metastatic patients or healthy volunteers. Further, we demonstrated that HSP70‐exosome levels correlated with the disease status and, when compared with circulating tumour cells, were more sensitive tumour dissemination predictors. Finally, our case studies indicated that HSP70‐exosome levels inversely correlated with response to the therapy and that, therefore, monitoring changes in circulating exosomal HSP70 might be useful to predict tumour response and clinical outcome.